Caged sister: art and resistance in American women’s prison zines 1933-2019 - Wright, Olivia (2020)
This thesis examines the previously unacknowledged literary tradition of women’s prison zines in the United States. Prison zines are short collections of art and literature that circulate in the prison where they are produced, in other penal facilities in America, and even among the general public. This thesis is grounded in an analysis of over fifty different publications and nearly 1000 individual issues that I have gathered over the course of my PhD through original archival research across the United States. I plot the entire women’s prison zine literary tradition from the earliest publication in 1933 through to the present day in an effort to identify shifts in content, readership and production. Using genre to define my approach, I examine how prison zines offer new insights into literary traditions that have otherwise excluded them, arguing that the prison is a unique environment for creative production that leads to a distinctive and compelling sub-genre of American literature. I examine how prison zines dismantle and adapt traditional women’s magazines, contribute to the American protest literature tradition, generate collective autobiography, and reconfigure feminist print culture in order to more accurately voice the experiences and identities of women behind bars. I identify three defining features of prison zines—community, confinement aesthetic and resistance—arguing that they are products of the unique carceral environment in which zines are produced: an environment rooted in punishment and isolation. This form of analysis demonstrates how incarcerated women use print to establish networks and sustain communities; voice marginalised experiences and opinions; educate each other and the general public; and communicate, create, and resist. In doing so, this thesis reflects the interdisciplinarity and growing diversification of the field of American Studies and the influence on it of gender, race, and print culture studies. It considers the historical contexts that create the genre, the literary and cultural techniques that define it, and articulates the marginalized voices that are continuously omitted from the canon.